Sequence analysis of TMEM173 exon 5 in patients with systemic autoimmune diseases. (2nd January 2016) - Balada, E.; Selva-O'Callaghan, A.; Felip, L.; Ordi-Ros, J.; Simeón-Aznar, C. P.; Solans-Laqué, R.; Vilardell-Tarrés, M.
Abstract: Background : Overactivation of the interferon pathways has been demonstrated in patients suffering from different systemic autoimmune diseases (SADs). Genetic associations have been described for many genes involved in these pathways. Gain-of-function mutations in the TMEM173 gene have recently been reported in patients with autoinflammatory diseases that share some clinical features with SADs. Methods : We aimed at detecting the reported three mutations of transmembrane protein 173 ( TMEM173 ) exon 5 in 100 patients suffering from: systemic lupus erythematosus (SLE) ( n  = 22), primary antiphospholipid syndrome (PAPS) ( n  = 20), systemic sclerosis (SSc) ( n  = 20), dermatomyositis (DM) ( n  = 20), and vasculitis ( n  = 18). Samples from 19 healthy controls were also included. Sequence analyses were performed from the derived TMEM173 exon 5 PCR fragment amplified from DNA obtained from whole blood. Results : Neither mutations nor single nucleotide polymorphisms (SNPs) in the exon 5 of the TMEM173 gene were detected. Just the rs7380272 SNP, located in the intronic region upstream exon 5, was detected in some patients and controls. The allele frequency of this SNP, though, was not statistically different between the patients groups and the control group. Conclusions : Our study demonstrates the lack of association between the presence of SADs and mutations in exon 5 of the TMEM173 gene. SADs are complex multifactorial diseases in which not just one but probably many different genetic alterations may coexist. Although we cannot rule out the possibility that other variations may exist in other regions of this gene, we think that studies must be directed towards the analysis of other genes which, as TMEM173, also code for nucleic acid sensors that activate the nucleic-acid induced type I IFN pathway.